To use or not to use electronic cigarettes? Reasons for use, stopping use and their behavioural sequelae among Mexicans who smoke - Gallegos Carrillo, Katia; Vidaña-Pérez, Dèsirée; Barrientos-Gutierrez, Inti; Arillo-Santillán, Edna; Cruz-Jiménez, Lizeth; Rodríguez-Bolaños, Rosibel; Thrasher, James F (Tobacco control, 2024)
IntroductionReasons for using and stopping the use of e-cigarettes and their associations with transitions in nicotine product use are relatively unknown in countries with e-cigarette bans, such as Mexico.MethodsData comes from an open cohort of people who smoke in Mexico, surveyed every 4 months from November 2018 to November 2021. Those who smoked and used e-cigarettes at time t (n=904 individuals, 1653 observations) were categorised at 4-month follow-up (t+1): (1) continued ‘dual use’, (2) exclusive smoking, (3) exclusive use of e-cigarettes or neither product. For people who formerly used e-cigarettes at time t (n=332 individuals, 372 observations), follow-up categories were: (1) continued exclusive smoking; (2) re-initiated e-cigarette use. Multinomial and logistic models regressed follow-up status (ref=status at time t) on reasons for using or stopping e-cigarette use, respectively, at time t, adjusting for covariates.ResultsThe most prevalent reasons for current e-cigarette use were ‘they were less harmful to others’ (40.5%) and ‘enjoyable’ (39.0%). Those who reported using e-cigarettes because they were less harmful to others (Adjusted Relative Risk Ratio (ARRR)=0.67), more enjoyable (ARRR=0.52), could help them to quit smoking (ARRR=0.65), or to control weight (ARRR=0.46) were less likely to return to exclusively smoking. Among people who formerly used e-cigarettes, lack of satisfaction was the primary reason for stopping e-cigarette use (32%) and those who reported this were less likely to start using e-cigarettes again at follow-up (Adjusted Odds Ratio (AOR)=0.58).ConclusionsSpecific reasons for using and stopping e-cigarettes predict changes in smoking and e-cigarette use, and targeting these beliefs could promote desired behaviour changes.